1998
DOI: 10.1089/thy.1998.8.377
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Features Associated with an Increased Risk of Thyroid Malignancy in Patients with Follicular Neoplasia by Fine-Needle Aspiration

Abstract: The application of fine-needle aspiration (FNA) to the evaluation of the thyroid nodule has greatly enhanced the ability of the clinician to appropriately select patients for thyroidectomy. However, despite extensive experience with thyroid FNA, the cytological distinction of benign from malignant follicular neoplasia remains problematic. As a result, most patients with FNA findings of a follicular neoplasm are referred for thyroidectomy. The goal of the present study was to develop clinical criteria capable o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

17
165
6
3

Year Published

2000
2000
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 265 publications
(191 citation statements)
references
References 17 publications
17
165
6
3
Order By: Relevance
“…[7][8][9][10] Many prognostic scoring systems ( [EORTC]) have been used to estimate diseasefree survival and cause-specific mortality in patients with thyroid cancer. [11][12][13][14] The main use of these risk classification systems is to identify patients with a poor prognosis, to ensure that they receive additional treatment such as radioiodine ablation, and to achieve closer follow-up monitoring.…”
mentioning
confidence: 99%
“…[7][8][9][10] Many prognostic scoring systems ( [EORTC]) have been used to estimate diseasefree survival and cause-specific mortality in patients with thyroid cancer. [11][12][13][14] The main use of these risk classification systems is to identify patients with a poor prognosis, to ensure that they receive additional treatment such as radioiodine ablation, and to achieve closer follow-up monitoring.…”
mentioning
confidence: 99%
“…1,2 In addition, clinical predictors of malignancy in patients with follicular neoplasms and HCN have been intensely studied, with varied results. [3][4][5][6][7][8] The cytomorphologic features of Hurthle cell nodules of the thyroid in FNAB have been described by multiple investigators, but there is limited agreement regarding the usefulness of specific features for the cytologic diagnosis of HCN. 9 -19 Kini et al 13 described a set of widely used criteria for the cytologic diagnosis of HCN that include cytoarchitecture, monomorphism, and macronucleoli.…”
mentioning
confidence: 99%
“…(16,18,19,25,26) According to the ATA guideline, initial total thyroidectomy is recommended in patients with indeterminate nodules who have large tumors (>4 cm) due to an increased risk for malignancy. Taneri et al (26) found in HCN that there was no malignancy among the tumors less than 1 cm diameter.…”
Section: Discussionmentioning
confidence: 99%